Community development through CSR activities of PT Solusi Bangun Indonesia, Tuban Plant in Tuban Regency, East Java, Indonesia - Bidari, Isnani Jana; Putriany, Noor Afifah; Wardhana, Rian Kusuma; Siswanto, Budi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2024)
The study of Corporate Social Responsibility (CSR) is of paramount importance. Creating a more comprehensive CSR program is a collective necessity for both companies and communities. Companies are expected to actively participate as development actors and to promote community welfare. This study aimed to assess the problems and potential of the community, prioritize CSR development programs, and formulate program recommendations based on the needs of the communities surrounding the company. This study employed qualitative method. The findings indicate personal and structural social issues in six villages within the company’s area. Each village possesses unique potentials that can be developed, including human resources, natural resources, economic resources, infrastructure resources, and social resources. Various programs can be developed based on the potential of each village. To ensure the success and sustainability of the planned CSR programs, an intensive and participatory approach must be undertaken, particularly with the beneficiaries. This approach should aim to foster trust, collaboration, and a shared vision and mission among all stakeholders involved in the program to ensure its success. Consequently, all parties involved can unite to collaboratively achieve the program’s goals and create a positive impact on the community and the surrounding environment.